2021
DOI: 10.1016/j.neo.2021.06.010
|View full text |Cite|
|
Sign up to set email alerts
|

Hedgehog/GLI1 Transcriptionally Regulates FANCD2 in Ovarian Tumor Cells: Its Inhibition Induces HR-Deficiency and Synergistic Lethality with PARP Inhibition.

Abstract: Ovarian cancer (OC) is one of the most lethal type of cancer in women due to a lack of effective targeted therapies and high rates of treatment resistance and disease recurrence. Recently Poly (ADP-ribose) polymerase inhibitors (PARPi) have shown promise as chemotherapeutic agents; however, their efficacy is limited to a small fraction of patients with BRCA mutations. Here we show a novel function for the Hedgehog (Hh) transcription factor Glioma associated protein 1 (GLI1) in regulation of key Fanconi anemia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…A study in Finland supports these findings by showing a significant association of variant (c.2715LJ+LJ1GLJ>LJA) in the FANCD2 gene with breast cancer (Mantere, 2017). Also, studies conducted in the United Kingdom and Poland on ovarian carcinoma samples verified that the risk of recurrence and death are highly associated with the expression level of FANCD2 (Moes-Sosnowska, 2019; Mani, 2021). On the other hand, in the United States, a study conducted on 181 ovarian cancer patients provided evidence of an increased survival rate in patients with FANCD2 mutation (Joshi, 2020).…”
Section: Discussionmentioning
confidence: 90%
“…A study in Finland supports these findings by showing a significant association of variant (c.2715LJ+LJ1GLJ>LJA) in the FANCD2 gene with breast cancer (Mantere, 2017). Also, studies conducted in the United Kingdom and Poland on ovarian carcinoma samples verified that the risk of recurrence and death are highly associated with the expression level of FANCD2 (Moes-Sosnowska, 2019; Mani, 2021). On the other hand, in the United States, a study conducted on 181 ovarian cancer patients provided evidence of an increased survival rate in patients with FANCD2 mutation (Joshi, 2020).…”
Section: Discussionmentioning
confidence: 90%
“…A study conducted in Finland supports these findings by showing a significant association of variant (c.2715 + 1G > A) in the FANCD2 gene with breast cancer [ 59 ]. Also, studies carried out on ovarian carcinoma samples verified that the risk of recurrence and death are highly associated with the expression level of FANCD2 [ 38 , 60 ]. In contrast, a study conducted on 181 ovarian cancer patients provided evidence of an increased survival rate in patients with the FANCD2 mutation [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mani et al Found that Hedgehog (Hh) / Glioma associated protein 1 (GLI1) was abnormally activated in some (Ovarian carcinosarcoma)OCS and affected the function of RF by regulating the transcription of FANCD2, thereby promoting DNA damage repair. Inducing the down-regulation of Hh / GLI1 can lead to HR repair deficiency, so it is related to improving resistance [ 52 ]. In addition, studies have found that mir-493-5p expressed in BRCA2 mutant cancer cells affects the stability of single-strand annealing (SSA), R-loops, and replication fork, which may lead to PARP inhibitor resistance.…”
Section: Parp Inhibitor Resistancementioning
confidence: 99%